US outlook and German confidence : does the confidence channel work? - Gustav Adolf Horn (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
One channel of business cycle shock transmission which gained attraction only recently is the confidence channel. The aim of the paper is to find out whether the confidence channel is actually working between the US and Germany. This is analysed using times series methods. In contrast to other studies the direct informational content of leading US indicators for German producer confidence and the significance of asymmetric reactions is tested. The results show that there is a relationship between the respective variables, which has become closer during the nineties. However the hypothesis of asymmetries had to be rejected.
Keywords: E37; 330; Confidence Channel; Business Cycle; Leading Indicators; Konjunkturzusammenhang; Konjunkturindikator; US-Amerikanisch; Geschäftsklima; Vertrauen; Deutsch; Vereinigte Staaten; Deutschland